Niñas y niños inimputables y facultades del juez penal ; Unimpeachable minors and powers of the criminal judge - Columba, Fabiola Daiana (2025)
En este artículo exhibiremos la doctrina que emana de precedentes judiciales de la provincia de Buenos Aires y del fuero Nacional y los fundamentos a favor de que un juez penal disponga de niños que se han inmiscuido en actividades delictivas y que resultan inimputables en razón de su edad. A la vez, exhibiremos las razones de otros que tienen una postura contraria, es decir, que niegan, a pesar de las normas expresas vigentes, esas facultades derivando el asunto al fuero civil o a los sistemas administrativos establecidos por las leyes de protección. In this article we will show the doctrine that emanates from judicial precedents of the province of Buenos Aires and the National Court and the grounds in favor of a criminal judge to dispose of children who have been involved in criminal activities and who are unimputable because of their age. At the same time, we will show the reasons of other that have a contrary position, that is to say, that deny, in spite of the express rules in force, those faculties, deriving the matter to the civil court or to the administrative systems established by the protection laws.